Evaluasi Pengajaran Siswa Kelas X Terhadap Pembelajaran Biologi - Adi Hartono; Shofi Azzahra Badres; Tri Vanesa; Enni Halimatussa’diah (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
This study aims to determine student learning outcomes in biology learning by evaluating the level of student knowledge by evaluating it using the Measurement Model. The method used in this study uses the evaluation method with the Measurement model, then the analysis technique used is the data analysis technique, namely quantitative descriptive by means of an Independent sample t-test. The population used in this study were all students of class X MIPA 1 and X MIPA 2 at Baitul Aziz Private High School in Deli Serdang Regency, totaling 58 students. Sampling in this evaluation study used a purposive sampling technique, with the research sample consisting of 28 students in class X MIPA 1 and class X MIPA 2 totaling 30 students. The results obtained in this study showed that the average value obtained in class X MIPA 1 was 59.8214. While the average obtained in class X MIPA 2 is 61.1667. Based on this, the average value obtained does not meet the KKM standard. Keywords: Evaluation, Teaching, Learning Biology